CORRELATION OF COMPUTERIZED TOMOGRAPHY (CT) SEVERITY SCORE FOR COVID-19 PNEUMONIA WITH CLINICAL OUTCOMES - Hilal, Kiran; Shahid, Jehanzeb; Ameen, Abullah; Seth Martins, Russell; Nankani, Avinash; Tanveer ul Haq; Arshad, Ainan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Though various computerized tomography (CT) severity scores have been described for risk prognostication for coronavirus disease 2019 (COVID-19), most are challenging to calculate and have variable inter-observer agreement. The objective of this study was to develop a simple CT severity score (CT-SS) with good inter-observer agreement and assess its correlation with clinical outcome. Methods: This retrospective study was conducted at the Aga Khan University Hospital (AKUH), from April-August 2020. All patients who were PCR positive for COVID-19 and underwent CT chest examination at AKUH were included. Severity of disease was described on the basis of a 10-point CT severity score (CT-SS) devised at our institution. CT-SS were categorized as Low (0-7) and High (8-10). Inter-observer reliability between radiologist and COVID-19 intensivist was assessed using the Kappa statistic. Results: A total of 73 patients were included, the majority male (58.9%) with mean age 55.8±13.93 years. The CT-SS rated on 0-10 showed substantial inter-observer reliability between radiologist and intensivist with a Kappa statistic of 0.78. Patients with CT-SS 8-10 had a significantly higher ICU admission & intubation rate (53.8% vs. 23.5%) and mortality rate (35.9% vs. 11.8%; p=0.017), as compared to those with CT-SS 0-7. Conclusion: We conclude that the described CT severity score (CT-SS) is a quick, effective, and easily reproducible tool for prediction of adverse clinical outcome in patients with COVID 19 pneumonia. The tool shows good inter-observer agreement when calculated by radiologist and physician independently.